Resolving inconsistencies and redundancies in declarative process models. (March 2017) - Di Ciccio, Claudio; Maggi, Fabrizio Maria; Montali, Marco; Mendling, Jan
Highlights: An approach for the automated detection of inconsistencies and redundancies in declarative process models is proposed. The solution to the problem is based upon the notion of product-automata monoid. The detection is made by checking the language emptiness and language inclusion of finite state automata. The implemented tool is integrated with a process discovery algorithm and available online. Abstract: Declarative process models define the behaviour of business processes as a set of constraints. Declarative process discovery aims at inferring such constraints from event logs. Existing discovery techniques verify the satisfaction of candidate constraints over the log, but completely neglect their interactions. As a result, the inferred constraints can be mutually contradicting and their interplay may lead to an inconsistent process model that does not accept any trace. In such a case, the output turns out to be unusable for enactment, simulation or verification purposes. In addition, the discovered model contains, in general, redundancies that are due to complex interactions of several constraints and that cannot be cured using existing pruning approaches. We address these problems by proposing a technique that automatically resolves conflicts within the discovered models and is more powerful than existing pruning techniques to eliminate redundancies. First, we formally define the problems of constraint redundancy and conflict resolution. Second, we introduce techniques based on the notion of automata-product monoid, which guarantees the consistency of the discovered models and, at the same time, keeps the most interesting constraints in the pruned set. The level of interestingness is dictated by user-specified prioritisation criteria. We evaluate the devised techniques on a set of real-world event logs.